Odpowiedzi

Najlepsza Odpowiedź!
2009-11-16T17:11:49+01:00
X(4x-3)=(2x-3)²


4x²-12=2x²-12x+9
4x²-2x²+12x=12-9
2x²+12x=3/÷x
2x+12=3
2x=-12+3
2x=-9/÷2
x=-4,5

x(0,04x-1,3)=(0,2x-1)²

0,04x²-1,3x=0,04x²-0,4x-1
0,04x²-1,3x-0,04x²+0,4x=1
-0,9x=1/÷(-0,9)
x=-1/9



Rozwiąz nierównosci i przedstaw rozwiazanie na osi liczbowej
a)(x-3)²<x(x-2)-x
x²-6x+9<x²-2x-x
x²-6x+9<x²-x
x²-6x-x²-x<9
-7x<9/÷(-7)
x<-9/7
x<-1,2/9

b)(3-x)²>(2-x)(6-x)
9-6x+x²>12+x²
-6x+x²-x²>-9+12
-6x>3/÷(-6)
x>-0,5


osi ci niestety nie zrobię...